Body physique and proportionality of Brazilian female artistic gymnasts - Bacciotti, S.; Baxter-Jones, A.; Gaya, A.; Maia, J. (Journal of Sports Sciences, 2017)
This study aimed to identify physique characteristics (anthropometry, somatotype, body proportionality) of Brazilian female artistic gymnasts, and to compare them across competitive levels (sub-elite versus non-elite) within competitive age-categories. Two hundred forty-nine female gymnasts (68 sub-elite; 181 non-elite) from 26 Brazilian gymnastics clubs, aged 9-20 years and split into four age-categories, were sampled. Gymnasts were assessed for 16 anthropometric traits (height, weight, lengths, widths, girths, and skinfolds); somatotype was determined according to Heath-Carter method, body fat was estimated by bioimpedance, and proportionality was computed based on the z-phantom strategy. Non-elite and sub-elite gymnasts had similar values in anthropometric characteristics, however non-elite had higher fat folds in all age-categories (P < 0.01). In general, mesomorphy was the salient somatotype component in all age-categories, and an increase in endomorphy, followed by a decrease in ectomorphy across age was observed. Regarding proportionality, profile similarity was found between sub-elite and non-elite within age-categories. In conclusion results suggest the presence of a typical gymnast`s physical prototype across age and competitive level, which can be useful to coaches during their selection processes in clubs and regional/national teams.